Transformasi Pembelajaran Pendidikan Agama Islam Berbantuan Artificial Intelligence di Era Digital : (Studi Kasus di Sekolah SMA Manba'ul 'Ulum) - Saehu Abas (PT. Pusmedia Group Indonesia, 2025)
This study aims to examine in depth the process of transforming Islamic Religious Education (IRE) teaching methods with the assistance of Artificial Intelligence (AI) at Manba'ul 'Ulum High School. A qualitative approach with a case study design was used in this study, with triangulation techniques through observation, in-depth interviews, and document analysis. Data validity is strengthened through strategies of credibility, dependability, confirmability, and transferability. The research findings reveal that the transformation of AI-assisted PAI teaching methods occurs through four stages: introduction and training, instructional design, limited implementation, and evaluation and refinement. The ideal integration model comprises four main components: AI-assisted learning content with Islamic values, adaptive learning methodologies, an analytics-based assessment system, and professional development programs for PAI teachers in AI technology. These findings are expected to contribute both conceptually and practically to the development of innovative, contextual, and competitive PAI learning in the digital age.